Computer networks forensics - Đokić, Ratomir Đ.; Markagić, Milorad S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Digital forensics is a set of scientific methods and procedures for collection, analysis and presentation of evidence that can be found on the computers, servers, computer networks, databases, mobile devices, as well as all other devices on which can store (save) data. Digital forensics, computer networks is an examination of digital evidence that can be found on servers and user devices, which are exchanged internal or external communication through local or public networks. Also there is a need for identifying sites and modes of origin messages, establish user identification, and detection types of manipulation by logging in to your account. This paper presents the basic elements of computer networks, software used to communicate and describe the methods of collecting digital evidence and their analysis.